ON PROGRESS OF NEW AMENDMENT OF NATIONAL RADIATION SAFETY STANDARDS DEVELOPMENT - I. K. Romanovich (Радиационная гигиена)
The article contains chronology of activity on the Radiation Safety Standards (RSS-99/2009) development; analysis ofevents andfactors having major influence on the document structure and contents is done. Most valuable additions and amendments introduced into the RSS-99/2009 in comparison with RSS-99 are outlined.